From the Sublime to the Monstrous. Two Interpretations of Kant - Angelucci, Daniela (Con-Textos Kantianos. International Journal of Philosophy, 2022)
The root of the noun monster (monstrum), derived from monere, to admonish, to warn, holds together the meaning of warning, to announce something that is out of the ordinary, against the natural order of things, with the meaning of showing, exposing – the root of monstrum is the same of the Italian verb mostrare (to show). Something announces itself, manifests itself as extraordinary, outside the normal course of events. On the other hand, the etymology of the noun prodigy (prod-igium) also expresses the sense of something that is ‘placed before’, exposed, shown. Which means that something particular, something that differs from the usual and natural order of things is exhibited, placed in front of a subject, causing astonishment and fear, disrupting one’s ability to represent. Starting from these two aspects – the feeling of fear and the break in the subject’s ordinary representational schema – the following pages aim to investigate the relationship between the monstrous and the concept of the sublime, linking them primarily as moments that challenge our cognitive possibilities.